Pediatric subspecialty outreach clinics: reach and impact on access to care - James C. Bohnhoff; Anya Cutler; Sean Hagenbuch; Kristen Kurland (BMC Pediatrics, 2024)
Abstract Background Recent research highlighting a shortage of pediatric subspecialists in the United States has shown wide variations in the distance from children to the nearest subspecialists but has not accounted for subspecialty outreach clinics, in which specialists may improve access in rural areas by periodically staffing clinics there. This study aimed to determine the impact of pediatric subspecialty outreach clinics on the driving times to the nearest pediatric subspecialists for children in Maine. Methods This cross-sectional study utilized administrative data on the schedule and location of pediatric subspecialty clinics in Maine in 2022 to estimate the driving time from each ZIP-code tabulation area to the nearest subspecialist, with and without the inclusion of outreach clinics. Using 2020 census data, we calculated the median and interquartile ranges of driving times for the state’s overall child population, as well as for children living in urban and rural areas. Results Of 207,409 individuals under 20 years old in Maine, 68% were located closer to an outreach location than to a clinical hub. Across the seven subspecialties offering outreach clinics, outreach clinics decreased median driving times to the nearest pediatric subspecialist by 5 to 26 minutes among all children, and by 16 to 46 minutes among rural children. Conclusions Pediatric subspecialty outreach clinics can substantially reduce the driving time to the nearest pediatric subspecialist , especially for children living in rural areas. The use of outreach clinics should be accounted for in research describing the geographic access or barriers to care. Expanding the number of outreach clinics should be considered by policymakers hoping to improve access.